Maxillary adenomatoid odontogenic tumor associated with a premolar - Kalia, Vimal (Medknow Publications & Media Pvt Ltd, 2015)
The adenomatoid odontogenic tumor (AOT) represents 3–7% of all odontogenic tumors, and over 750 cases have been reported in the literature. This lesion was formerly considered to be a variant of the ameloblastoma and was designated as adenoameloblastoma. These lesions may infrequently produce dentinoid material and rarely enamel matrix. Consequently, the WHO (2005) classification of odontogenic lesions considered this process to represent a mixed odontogenic neoplasm. We present a case of a 12-year-old female patient with an AOT of diameter 5 cm × 5 cm located in the anterolateral region of the maxilla in association with an impacted premolar tooth. The rarity of AOT, association of this lesion with regards to maxillary premolar, the exaggerated size at presentation, the eruption of the displaced canine postoperatively and uneventful healing of the bony defect without adjunctive therapy makes this case unique.